OPPORTUNITIES AND CHALLENGES IN MODELING AN ENVIRONMENTAL MANAGEMENT SYSTEM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The business ecosystem provides full integration of economic and environmental objectives. Every company, including those from the Bulgarian mining industry, implements specific actions, mechanisms, innovations for environmental management. The aim of the present study is to analyse the relationship between the economic and non-economic priorities of enterprises of the mining industry, especially now in the context of solving the global problem of transformation towards sustainable development. The following research tasks have to be settled for reaching the above-mentioned goal: 1. to analyze the influence of modern technologies, the remote control of machines underground, including remote control and self-learning drones in underground mines on the optimization and improvement of work processes and the protection of a cleaner environment; 2. to focus on some relevant aspects of green transformation of the mining industry, incl. in the development of environmental, social and new management models as a factor for successful business; 3. to research the impact of the initiated cycle of interest rate tightening on the implementation of the planned activities for environmental management of the mining industry. In the course of the study shall be justified the thesis that the future of the mining industry in Bulgaria is digital, green and sustainable. The methodology of structured interview was used. The sample was formed by the method of random non-recurrent selection. For the purposes of the research, we have carried out analysis of the whole assessment of the favourable opportunities and potential risks, as well as the strengths and weaknesses of the new model for an environmental management system. The results of the research are expressed in establishing the trend for digitalization and innovation, tracking the importance of environmental management and protection.